Hydantoins Derived from Ketopinic and 4-camphorcarboxylic Acids - Knizhnikov, Volodymyr; Voitenko, Zoia; Gorichko, Marian (Київський національний університет імені Тараса Шевченка, 2013)
Diastereospecific formation of hydantoins from ketopinic and 4-camphorcarboxylic acids under Bucherer-Bergs reaction conditions has been investigated. The easiness of this transformation provides a straightforward synthetic pathway to enantiopure conformationally rigid amino acids derivatives, as well as functionalized hydantoins, starting from inexpensive and easily available natural camphor.
Keywords: Hydantoins; ketopinic; 4-camphorcarboxylic acid